1981
DOI: 10.3109/10826088109038899
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Program Clients and Emergency Room Patients: A Comparison of Two Drug-Using Samples

Abstract: Research on institutionalized drug abusers has produced a profile of drug users which at times has been applied improperly to all individuals who manifest drug-related problems. This study compares a sample of drug treatment clients with a sample of emergency room patients who have acute drug reaction problems to ascertain the extent to which the traditional profile of drug abusers accurately describes both of these drug-using groups. The conclusion is that the treatment client sample does resemble the profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…If the effect of drug law enforcement on treatment entry is cumulative, a history of contact with police and/or the criminal justice system should predict treatment experience. Chitwood & Chitwood (1981) compared the characteristics of 206 randomly chosen drug users in long-term treatment for drug dependence and 103 randomly chosen patients attending a county emergency room for the treatment of an acute drug-related problem. Bivariate comparisons showed that those in the long-term treatment programme were much more likely to have an arrest record than those attending an emergency room for treatment of acute drug problems.…”
Section: Introductionmentioning
confidence: 99%
“…If the effect of drug law enforcement on treatment entry is cumulative, a history of contact with police and/or the criminal justice system should predict treatment experience. Chitwood & Chitwood (1981) compared the characteristics of 206 randomly chosen drug users in long-term treatment for drug dependence and 103 randomly chosen patients attending a county emergency room for the treatment of an acute drug-related problem. Bivariate comparisons showed that those in the long-term treatment programme were much more likely to have an arrest record than those attending an emergency room for treatment of acute drug problems.…”
Section: Introductionmentioning
confidence: 99%